Características socioeconômicas e demográficas associadas à perda de excesso de peso em pacientes submetidos à cirurga bariátrica - Picoli, Priscila Sales [UNESP] (2015)
Nowadays, obesity is considered a serious public health problem that affects all populations. It is related to all the aspects of human conditions - social, emotional, and health - caused by overweight. When the clinical treatment for severe obesity is not effective, bariatric surgery becomes an option, as it has shown positive results in weight loss and maintenance. A descriptive and a cross sectional study was carried out with patients submitted to bariatric surgery at the Clinical Hospital Botucatu School of Medicine. The aim was to describe the socioeconomic and demographic characteristics associated with the results of weight loss, and to assess quality of life through the BAROS (Bariatric Analysis and Reporting Outcome System) protocol. We used a sample of 131 patients submitted to bariatric surgery in outpatient followup. Patients were classified into two groups considering the 50th percentile for achieved success and non-achieved success. In the preoperative period, the patients' BMI (Body Mass Index) corresponded to class III obesity, above 40 kg/m2. In the postoperative period, all patients had a reduction in the BMI and minimization of the comorbidities. Socioeconomic and demographic variables indicate that level of education and age group are related to higher weight loss, while per capita income was associated with lower weight loss. There was no association between the investigated variables and the result of the BAROS protocol. Therefore, the improvement in quality of life after bariatric surgery is not affected by socioeconomic and demographic factors. However, higher level of education, lower age and lower per capita income are associated with higher weight loss